Industrial employment expansion under alternative development strategies - R. Banerji; J. Riedel (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1977)
The general consensus in recent literature on development economics is that outward-looking strategies are likely to create more employment opportunities in labour abundant countries than inward-looking strategies. The reasons generally given to support this contention are (i) that inward-looking strategy limits the scope for structural change into relatively labour-intensive branches and (ii) that policies associated with inward-looking strategy tend to distort factor prices thereby giving incentive to the adoption of relatively capital-intensive techniques of production. This paper develops an identity which delineates the components of industrial employment expansion into effects of: (i) productivity change, (ii) capital accumulation and (iii) change in the composition of manufacturing. Applying this identity to India and Taiwan, two countries that have taken very different paths towards economic development, provides some insight into the source of employment expansion and its stringent limitations under alternative development strategies.
Keywords: 330